"It's about fitting in with the organization": A qualitative study of employers of nurse practitioners - Leidel, S.; Hauck, Yvonne; McGough, Shirley (Wiley-Blackwell Publishing, 2018)
AIMS AND OBJECTIVES: To explore the views of employers about the value nurse practitioners (NPs) add to health services, enablers and barriers to employing NPs, and intentions to employ NPs or expand NP services in the future. BACKGROUND: Research on Australian NPs has focused on NPs' experiences or patient-related factors like waiting times. Few studies have explored NP roles from the perspective of employers. Australian NPs employed by the private sector are eligible for reimbursement by the national health insurance scheme (Medicare Australia), potentially generating revenue for employers and broadening their career opportunities. We aimed to explore private sector employers' views on the barriers and facilitators to employing NPs and to identify factors affecting NP employability. DESIGN: A qualitative descriptive exploratory study. METHOD: Employers of NPs from 23 private and non-profit health services in Western Australia were interviewed. Inductive content analysis was used to explore the data. RESULTS: Enablers to employing an NP included enhanced customer service and improved health outcomes. Barriers to employing an NP included lack of financial benefit and inadequate experience or qualifications. Employers also identified future directions for NP employability, such as filling a gap that added value to the health service. CONCLUSIONS: Employers wanted NPs to work toward a shared vision of patient care that aligned with organizational needs. RELEVANCE TO CLINICAL PRACTICE: Findings can inform NP education and workforce planning to optimally meet employer and patient health needs. This article is protected by copyright. All rights reserved.